2004
DOI: 10.1007/s10340-004-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated and delayed exposure to codling moth eggs on reproduction of Trichogramma cacoeciae and T. principium (Hymenoptera: Trichogrammatidae) females

Abstract: Laboratory experiments were conducted to evaluate the influence of repeated and delayed exposure to fresh codling moth eggs on the parasitism of Trichogramma cacoeciae Marchal and T. principium Sug. et Sor. The percentage survival of T. cacoeciae and T. principium females significantly declined as the number of exposure times increased (or as the females became older). The highest mean number of parasitized eggs and F 1 progeny were recorded during the first day of exposure, after which they declined. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…We assumed that TO females deprived from A. pernyi host for such a long period of time (i.e., more than 4 days) resulted in intensive oosorption and consequently the parasitization ability of TO females decreased. The variation in multiparasitism rates in our results did confirm that parasitism ability of TO on A. pernyi host was largely age dependent (Fleury and Bouletreau 1993;Godfray 1994;Garcia et al 2001;Makee 2005;Huang et al 2017).…”
Section: Trichogramma Ostriniae Age Impacts On Multiparasitismsupporting
confidence: 78%
See 1 more Smart Citation
“…We assumed that TO females deprived from A. pernyi host for such a long period of time (i.e., more than 4 days) resulted in intensive oosorption and consequently the parasitization ability of TO females decreased. The variation in multiparasitism rates in our results did confirm that parasitism ability of TO on A. pernyi host was largely age dependent (Fleury and Bouletreau 1993;Godfray 1994;Garcia et al 2001;Makee 2005;Huang et al 2017).…”
Section: Trichogramma Ostriniae Age Impacts On Multiparasitismsupporting
confidence: 78%
“…Therefore, in the context of possible development of mass production of T. ostriniae using a multiparasitism-based method, further experiments are needed to evaluate how factors such as parasitoid age could modulate emergence rate from A. pernyi host (during multiparasitism). Several studies demonstrated that Trichogramma parasitoid age could impact parasitism and progeny emergence from different host eggs in monoparasitism (Garcia et al 2001, Hegazi andKhafagi 2001;Hohmann and Luck 2004;Makee 2005;Ayvaz et al 2008;Pizzol et al 2012). However, parasitoid developmental rates and agerelated oviposition patterns (syn-ovigenic or pro-ovigenic) could also have influence on the outcomes of multiparasitism between parasitoids (Cusumano et al 2012;Harvey et al 2013).…”
mentioning
confidence: 99%